Study on the performance of subsurface flow and free water surface constructed wetland for landfill leachate treatment - Ain Nihla, Kamarudzaman; Johan, Sohaili, Prof. Madya Dr.; Mohd Faizal, A. J. (Universiti Sains Malaysia (USM), 2011)
4th International Conference on Recent Advances in Materials, Minerals and Environment and 2nd Asian Symposium on Minerals and Processing (RAMM & ASMP 2009) organized by Universiti Sains Malaysia (USM), Japan Society of Mechanical Engineers, Institute of Materials Malaysia (Northen Region), Advanced Materials Processing and Intergrity Group UKM, Malaysian Chambers of Mine and Institute of Minerals Engineer, 1st - 3rd June 2009 at Bayview Beach Resort, Penang.